Supporting a Learning System in Pediatric Emergency Pathways: Using Organizational Comparisons, Serious Incidents, and Near-Miss Events to Improve the Diagnosis and Treatment of Testicular Torsion. Issue 7 (29th July 2022) - Winters, David Adam; Mehmi, Ashley K.; Menzies-Wilson, Richard; Folkard, Samuel S.; Ryan, Kate; Sevdalis, Nick; Green, James S.A.
Abstract : Background: Scrotal pain is a common presentation to the emergency department requiring prompt investigation and management to identify testicular torsion and increase the opportunity for testicular salvage. Using national data obtained from the NHS Improvement, we aim to identify key suboptimal areas in the acute diagnosis and management of testicular torsion with a view to learning from these and improving outcomes. Methods: A freedom of information request was made to all 134 hospital groups in England and Wales that manage testicular torsion. Serious incidents experienced by these hospitals were analyzed to see whether those with pediatric emergency departments fared better than those without. In addition, a qualitative thematic analysis of the NHS Improvement National Reporting and Learning System database over a 12-year period (2007–2019) was undertaken, to identify common themes associated with orchidectomies and "near-miss" events in the pediatric population. Results: Three hundred four patient safety incidents were returned and divided into 62 orchidectomies and 242 near-miss events. The most common factor in the orchidectomy group was individual factors (83.9%). Misdiagnosis of symptomatic testicle was not significant when comparing ED to specialist surgeons (odds ratio = 1.46, P = 0.3842). Atypical presentation resulting in orchidectomy was significant when comparing ED with specialists (odds ratio = 6, P = 0.0355). Near-miss events, not leading to orchidectomy, are often due to a wider variety of factors. A Mann-Whitney U test showed that there was no statistical significance in incidents when comparing general ED units caring for all ages with pediatric EDs in terms of incidents ( U = 807.5, z = −1.124, P = 0.261). Conclusions: There is a need for education in ED about atypical presentation of testicular torsion and examination of scrotum in cases of lower abdominal pain. It is also vital that specialist teams are cognizant of the standard operating procedures relevant to scrotal pain and testicular within the organization and the wider clinical network. Finally, there should be a drive for annual collation of data in urology and ED units with regards to testicular torsion as patient safety incidents may be underreported.